Limitation of Indonesian Administrative Criminal Law For Pandemic Treatment Against Health Protocols Violation - Firman Arif Pribadi; Nurus Zaman; Eny Suastuti (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Criminal Law to deal with Corona Virus Disease 2019 (Covid-19) is under the spotlight during the handling of the pandemic. Criminal Law is intended to be used when the patient's moral responsibility to declare that he has been abroad having not been fulfilled, and the government's health protocols are ignored. Meanwhile, various laws for Covid-19 pandemic treatment does not provide strict norms; on the contrary, it is sometimes using blanket offence formulation. This study explores the limits of Administrative Criminal Law in the health sector and pandemic management to impose penalties for health protocols violation. Using the normative systematic interpretation method, the study results show no difference formulation of criminal law norms in special laws, which are administrative with criminal law norms in special laws. However, the difference exists within the theoretical realm. Administrative criminal law is not aimed at free individuals and is not socially and psychologically illegal. Still, it is aimed at humans as players of particular roles required to conform with other forms of action according to their role. Unfortunately, administrative criminal law exists outside the Criminal Code, primarily aimed at freeing individuals and socially and psychologically illegal. Law enforcement practices cannot provide a gradation for these two groups of laws—conditions where the fundamental rights of citizens are threatened by the power to impose penalties. This study proposes broadening justification and excuse in the Indonesian Criminal Code, which is appropriate for the character of administrative criminal law.Keywords: Blanket Offence Formulation; Excuse; Justification AbstrakHukum Pidana untuk Penanganan Corona Virus Disease 2019 (Covid-19) menjadi sorotan selama penanganan pandemi. Hukum Pidana dimaksudkan untuk digunakan ketika tanggung jawab moral pasien untuk menyatakan bahwa ia telah di luar negeri belum terpenuhi, dan protokol kesehatan pemerintah diabaikan. Sementara itu, berbagai undang-undang penanganan pandemi Covid-19 tidak memberikan norma yang tegas; sebaliknya, kadang-kadang menggunakan rumusan blanket offence. Kajian ini menelusuri batasan Hukum Pidana Administrasi di bidang kesehatan dan manajemen pandemi untuk menjatuhkan sanksi bagi pelanggaran protokol kesehatan. Dengan menggunakan metode interpretasi sistematis normatif, hasil penelitian menunjukkan tidak ada perbedaan rumusan norma hukum pidana dalam undang-undang khusus yang bersifat administratif dengan norma hukum pidana dalam undang-undang khusus. Namun, perbedaannya ada dalam ranah teoretis. Hukum pidana administrasi tidak ditujukan untuk individu yang bebas dan tidak ilegal secara sosial dan psikologis. Namun, itu ditujukan pada manusia sebagai pemain peran tertentu yang diperlukan untuk menyesuaikan diri dengan bentuk tindakan lain sesuai dengan perannya. Sayangnya, hukum pidana administrasi ada di luar KUHP, terutama ditujukan untuk membebaskan individu dan ilegal secara sosial dan psikologis. Praktik penegakan hukum tidak dapat memberikan gradasi bagi kedua kelompok hukum ini—kondisi di mana hak-hak dasar warga negara terancam oleh kekuasaan untuk menjatuhkan hukuman. Penelitian ini mengusulkan perluasan justifikasi dan dalih dalam KUHP Indonesia, yang sesuai dengan karakter hukum pidana administrasi.Kata Kunci: Formulasi Blanket Offense; Mengizinkan; Pembenaran